2022
DOI: 10.3390/cells11060928
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Tissue-Derived Mast Cells (MC) as Experimental Surrogate for In Vivo Connective Tissue MC

Abstract: Bone-marrow-derived mast cells are matured from bone marrow cells in medium containing 20% fetal calf serum (FCS), interleukin (IL)-3 and stem-cell factor (SCF) and are used as in vitro models to study mast cells (MC) and their role in health and disease. In vivo, however, BM-derived hematopoietic stem cells account for only a fraction of MC; the majority of MC in vivo are and remain tissue resident. In this study we established a side-by-side culture with BMMC, fetal skin MC (FSMC) or fetal liver MC (FLMC) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…However, it is advantageous to use ex vivo skin MCs at least in a few experiments, to verify findings obtained with the precultured counterparts. The notion that expanded cells will resemble their respective prototype cell in the original tissue, even after culture, was recently reported also for mouse fetal skin or fetal liver-derived MCs [61]. However, our findings demonstrate a number of slightly unusual features that should be taken into consideration when using the in vitro-expanded human skin MCs in studies of MC biology (Figures 4 and 5).…”
Section: Discussionsupporting
confidence: 68%
“…However, it is advantageous to use ex vivo skin MCs at least in a few experiments, to verify findings obtained with the precultured counterparts. The notion that expanded cells will resemble their respective prototype cell in the original tissue, even after culture, was recently reported also for mouse fetal skin or fetal liver-derived MCs [61]. However, our findings demonstrate a number of slightly unusual features that should be taken into consideration when using the in vitro-expanded human skin MCs in studies of MC biology (Figures 4 and 5).…”
Section: Discussionsupporting
confidence: 68%
“…However, it is advantageous to use ex vivo skin MCs at least in a few experiments, to verify findings obtained with the precultured counterparts. The notion that expanded cells will resemble their respective prototype cell in the original tissue, even after culture, was recently reported also for mouse fetal skin or fetal liver-derived MCs [ 61 ]. However, our findings demonstrate a number of slightly unusual features that should be taken into consideration when using the in vitro-expanded human skin MCs in studies of MC biology ( Figure 4 and Figure 5 ).…”
Section: Discussionmentioning
confidence: 97%
“…The mouse BMMCs originate from adult bone marrow, whereas the majority of human skin MCs have their origin primarily in an early wave of cells from the yolk sac [ 27 , 28 ]. A recent study of MCs from different mouse organs has shown that, also in the mouse, the organ of origin is a decisive factor for the resulting MC phenotype even though cells from different sources were exposed to identical microenvironments during their recent history [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This novel approach was able to differentiate MCs from other immune cells, including basophils and eosinophils, and to reveal a unique mouse and human MC identity [ 26 , 27 , 28 ]. Moreover, the presence of distinct MC subsets in different connective tissues has been elucidated [ 29 , 30 ], revealing a high degree of MC heterogeneity [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%